QARAQALPAQ JUWAP AYTISLARINIŃ JANRLIQ HÁM KÓRKEMLIK ÓZGESHELIKLERI - Bazarbaeva, B. (SCIENCE and SOCIETY, 2022)
In the article, one of the richest samples of the Karakalpak people, the genre and artistic features of juwap aytis are studied.